2018
DOI: 10.3390/su10030789
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Ecotourism Behavior: Independent and Interdependent Self-Construals, Ecological Belief, Willingness to Pay for Ecotourism Services and Satisfaction with Life

Abstract: The purpose of this study is to investigate the antecedents related to why tourists engage in ecotourism and the consequences of ecotourism behavior. This study examined the concept of self-construal as a social aspect of self that influences different levels of ecological beliefs, which, in turn, affect ecotourism behavior. To address the unsatisfactory predictive power of the belief/attitude-behavior model, this study included the willingness to pay (WTP) for ecotourism between the ecological belief and ecot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 83 publications
2
29
1
1
Order By: Relevance
“…Among the 401 respondents considered in the analysis, there were 211 purchasers and 190 non-purchasers. We estimated the significance of the differences between the two groups by comparing the χ 2 statistics of the cross-group equality of the constrained and unconstrained models [79,80]. The χ 2 difference test was barely significant except in constrained models 1 and 2 ( Table 6).…”
Section: Moderating Effects Of Purchase Experiencementioning
confidence: 99%
“…Among the 401 respondents considered in the analysis, there were 211 purchasers and 190 non-purchasers. We estimated the significance of the differences between the two groups by comparing the χ 2 statistics of the cross-group equality of the constrained and unconstrained models [79,80]. The χ 2 difference test was barely significant except in constrained models 1 and 2 ( Table 6).…”
Section: Moderating Effects Of Purchase Experiencementioning
confidence: 99%
“…In this sense, habit strength is the degree of automaticity a behaviour has in a given stable situation [45]. The environmental attitude-behaviour gap is frequently studied in the literature [22,30,[82][83][84][85][86]. However, the relationship between environmental habits and attitude or behaviour has received marginal attention.…”
Section: Hypothesis 3b (H3b)mentioning
confidence: 99%
“…In this sense, Roberts and Bacon [67] suggested that the past research had suffered from poor attitude-behaviour consistency. Currently, researchers are also challenged by the gap between ecological attitudes and corresponding behaviours [68][69][70][71][72]. Hence, the usual findings reveal either a moderate relationship between environmental attitude and behaviour [73][74][75][76][77], or a weak relationship [78][79][80][81].…”
Section: Research Model and Hypotheses Testingmentioning
confidence: 99%